TEXTURE SYNTHESIS BY GENETIC ALGORITHM (Journal of Engineering, 2007)
One way to synthesis texture in a fast and easy way is image quilting proposed by Efros and Freeman in2001. This research brings the adaptive search power of genetic algorithm and combines it with theconcept of image quilting to propose new texture synthesis algorithm. The proposed GA is ran on manydifferent images from standard texture sets. Visual comparison of our proposed GA with image quiltingalgorithm is considered. The texture results generated by the proposed GA are roughly comparable inquality to those generated from Efros and Freeman algorithm.